2015
DOI: 10.1111/dth.12273
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of moderate and severe adult chronic atopic dermatitis with narrow-band UVB and the combination of narrow-band UVB/UVA phototherapy

Abstract: The phototherapy is a safe and effective technique for the treatment of adult patients with atopic dermatitis (AD). The treatment of chronic forms of the disease is most often done with narrow-band UVB (NB-UVB). There also exist effective phototherapy options against the AD. The aim of this study was to asses if the combination of NB-UVB with UVA was more effective than the treatment with only NB-UVB against adult chronic AD. We carried out a prospective and observational study. Adult patients with chronic AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…As a rule, phototherapy is not indicated in the acute stage of AD (except UVA1, which is also effective in managing AD flares) [3840], but is more apt to treat chronic, pruritic, lichenified forms [24, 35], and should not be prescribed in those patients who experience a worsening of their dermatosis during sun exposure as in the case of other common chronic inflammatory diseases such as psoriasis [41]. In general, NB-UVB has been indicated for chronic-moderate forms of AD and is currently preferred to broadband UV because it is less erythemogenic; a recent study reported that the combination with UVA did not show any further benefits [42]. On the other hand, medium-dose UVA1 appears to be similar to NB-UVB in terms of efficacy, as shown in different studies [43, 44].…”
Section: Methodsmentioning
confidence: 99%
“…As a rule, phototherapy is not indicated in the acute stage of AD (except UVA1, which is also effective in managing AD flares) [3840], but is more apt to treat chronic, pruritic, lichenified forms [24, 35], and should not be prescribed in those patients who experience a worsening of their dermatosis during sun exposure as in the case of other common chronic inflammatory diseases such as psoriasis [41]. In general, NB-UVB has been indicated for chronic-moderate forms of AD and is currently preferred to broadband UV because it is less erythemogenic; a recent study reported that the combination with UVA did not show any further benefits [42]. On the other hand, medium-dose UVA1 appears to be similar to NB-UVB in terms of efficacy, as shown in different studies [43, 44].…”
Section: Methodsmentioning
confidence: 99%
“…Given the response of atopic eczema to several types of light-based therapy and if NB-UVB phototherapy fails or there is early relapse after discontinuation of treatment, then the options of either PUVA or UVA1 exist, although given the lack of evidence of superiority of UVA1, the latter would likely only be considered if PUVA was contraindicated. Indeed, a combination of NB-UVB and UVA or UVA1 could be considered for some patients, although whether this is advantageous compared with UVB alone is unclear and this needs further study ( 58 ).…”
Section: Eczemamentioning
confidence: 99%
“…Since narrow‐band UVB (NB‐UVB) treatment became the option of choice for many skin conditions including AD , it is difficult to compare cumulative doses between artificial and natural UVB doses. The same remark can be done regarding UVA doses, as UVA is never used solely but only with prior additional psoralen intake, orally or in bath or together with NB‐UVB .…”
Section: Discussionmentioning
confidence: 99%